2021
DOI: 10.1242/dmm.047001
|View full text |Cite
|
Sign up to set email alerts
|

Transformed notochordal cells trigger chronic wounds in zebrafish, destabilizing the vertebral column and bone homeostasis

Abstract: Notochordal cells play a pivotal role in vertebral column patterning, contributing to the formation of the inner architecture of intervertebral discs (IVDs). Their disappearance during development has been associated with reduced repair capacity and IVD degeneration. Notochord cells can give rise to chordomas, a highly invasive bone cancer associated with late diagnosis. Understanding the impact of neoplastic cells during development and on the surrounding vertebral column could open avenues for earlier interv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…This, afterwards, can lead to spinal malformations, as notochord abnormalities are associated with vertebral defects. Furthermore, it is described that the notochord, in particular the notochordal cells, plays a crucial part in vertebrae development and intervertebral disc formation, as their disappearance is linked to reduced repair capacity and intervertebral disc degeneration [26][27][28][29][30]. We expected to see similarities between old and deformed N. furzeri, as in human degenerative spine diseases and mammalian aging, a degradation of the intervertebral discs can be observed.…”
Section: Discussionmentioning
confidence: 88%
“…This, afterwards, can lead to spinal malformations, as notochord abnormalities are associated with vertebral defects. Furthermore, it is described that the notochord, in particular the notochordal cells, plays a crucial part in vertebrae development and intervertebral disc formation, as their disappearance is linked to reduced repair capacity and intervertebral disc degeneration [26][27][28][29][30]. We expected to see similarities between old and deformed N. furzeri, as in human degenerative spine diseases and mammalian aging, a degradation of the intervertebral discs can be observed.…”
Section: Discussionmentioning
confidence: 88%
“…Examples include live images of reporter lines labeling osteoblasts, live staining with Alizarin Red to label the bones. ( B ) Images of volume rendering from micro-computed tomography (uCT) of adult WT and mutant (chordoma model [ 90 ]), as an example of skeletal abnormalities in mutants (vertebral fusion and lower TMD). Variations of TMD are shown color-coded.…”
Section: Figurementioning
confidence: 99%
“…In the four decades since the discovery of RAS mutations in cancer, researchers have made significant advances in understanding their mechanistic underpinnings. For example, work previously published in DMM has shown that dysregulated RAS signaling affects phenotypic plasticity ( Bangs et al, 2020 ; López-Cuevas et al, 2021 ), an emerging hallmark of cancer ( Hanahan, 2022 ). Several such interdisciplinary studies focus on the oncogenic output of dysregulated RAS signaling and provide essential bases for identifying actionable therapeutics.…”
Section: Ras Targeting In Cancermentioning
confidence: 99%